Impact of fuel cell range extender powertrain design on greenhouse gases and NOX emissions in automotive applications. (15th November 2021) - Desantes, J.M.; Novella, R.; Pla, B.; Lopez-Juarez, M.
Abstract: Fuel cell (FC) technologies for mobility are gaining interest as promising options to decarbonize the transport sector in line with the current progress towards the H2 economy. Previous studies show how the fuel cell range extender (FCREx) powertrain architecture can offer flexible and efficient operation along with the potentially low total cost of ownership (TCO) in passenger car applications. Cradle-to-grave emissions of these vehicles have not been estimated, nor their variation with the components sizing or the H2 production pathway analyzed. In this study, the life cycle assessment (LCA) and sizing methodologies were combined to address these knowledge gaps. The design spaces were generated by varying the FC maximum power, the battery capacity and the H2 tank capacity and by simulating the resulting designs with the WLTC 3b driving cycle. Then, the lifetime H2 and energy consumption results and design parameters were calculated and used as inputs to estimate the greenhouse gases (GHG) and NOX emissions on the manufacturing and fuel production cycles. From the results, it was proven how considering steam methane reforming (SMR) with carbon capture and storage (CCS) as the H2 production pathway could decrease by 60% and 38% GHG-100 and NOX emissions respectively, with respect to electrolysis where electricity is generated with the EU mix. The optimum design, in terms of emissions, was found to be with low-moderate battery capacity and moderate-high FC maximum power in contrast to the optimum design for performance, which had high battery capacity and high FC stack power. Highlights: A novel approach using sizing and LCA methodologies is used for passenger FCREx. Design spaces for FCREx vehicles showing GHG-100, NOX and performance are generated. Production pathways for H2 were electrolysis with the EU mix, SMR and SMR with CCS. GHG-100 & NOX emissions may vary up to 10% when comparing the worst and best designs. Emissions-wise and performance-wise optimum FCREx designs are compared